Study of Proportion of Mustard Green (Brassica juncea) with Cassava Tape and Concentration of Sucrose on Ice Cream Properties - Pramesti Regita; Lukman Hudi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine effect of proportion mustard green with cassava tape and concentration of sucrose on the characteristic of ice cream. The study was conducted from February until April 2020, used factorial randomized block design (RBD). The first factor was proportion of mustard green and cassava tape that consists P1 (25% mustard green, 75% tape), P2 (50% mustard green, 50% tape) and P3 (75% mustard green, 25% tape). Second factor was concentration of sucrose wich consist S1 (10%), S2 (15%) and S3 (20%). The data was analyzed used analysis of variance and further test was HSD 5%. Organoleptic test used analysis non parametric Friedman and the best treatmen used effectiveness index. The result showed there was interaction between the proportion of mustard green with tape and concentration of sucrose on greenness value of ice cream. Proportion of mustard green with tape had significant affected on protein content, fiber content, overrun and melting point. Concentration of sucrose had significant affected on protein content of ice cream. Organoleptik test showed significant affected on aroma, color, texture and taste of ice cream. The best treatment was proportion 75% mustard green, 25% tape and concentration of sucrose 15% wich characteristic of protein content 1,173%, fiber content 11,386%, overrun 30,667%, melting point 7,511 minutes/10 gram, color L*a*b (62,460*-8,068*25,333) and organoleptic test of color 3,100, aroma 3,967, texture 4,100, taste 4,567 and overall acceptance 4,167 (like-very like).